PEMANFAATAN TEH KOMBUCHA SEBAGAI OBAT HIPERURISEMIA MELALUI PENURUNAN KADAR 8-HIDROKSI-2-DEOKSIGUANOSIN - Jayadilaga, Made Baruna; Manuaba, Ida Bagus Putra; Rustini, Ni Luh (Jurnal Kimia (Journal of Chemistry), 2014)
The utilization of kombucha tea as hyperuricemia medicine by decreasing levels of 8-hydroxy-2-deoksiguanosin (8-OHdG) has been carried out. This study aimed to determine the ability of kombucha tea to decrease uric acid and 8-OHdG levels in hyperuricemia rats. This research is true experimental with posttest only control group design. Rats that had experienced hyperuricemia were given kombucha tea dose of 10 mL/kg body weight and 40 mL/kg body weight of 4, 8, and 12 days fermentation period. The results showed that kombucha tea can decrease uric acid and 8-OHdG levels in hyperuricemia rats. The best dose of kombucha tea in decreasing uric acid and 8-OHdG levels was 40 mL/kg body weight with 8 days fermentation period. The decrease of uric acid and 8-OHdG levels were 93.88% and 85.89% respectively.
Keywords: Kombucha tea, uric acid, hyperuricemia, oxidative stress, 8-OHdG